IMPACT OF COVID-19 ON DELIVERING QUALITY AGRICULTURAL EDUCATION: CONTEMPORARY ISSUES AND PROSPECTS IN NORTH EAST, NIGERIA (Unilorin Journal of Lifelong Education, 2023)
This paper discussed impact of COVID-19 on delivering quality agricultural education in North East Nigeria and specifically emphasized contemporary issues that emanate as a result of the pandemic, and identified possible prospects beyond COVID-19. The paper highlighted that the impact of COVID-19 in agricultural education are negative and have different dimensions, and are more significantly detected on teachers, learners and their households. The paper also detected multidimensionality of issues that manifested as a result of COVID19 pandemic in agricultural education to include social; economic; psychological and ICT issues. However, despite the challenges of COVID-19, agricultural education in North East Nigeria has brighter prospects that can be futuristically viewed through the opportunities created which are: increase in awareness; increase in job spaces; possibilities of enhancing e-agriculture; facilitating e-trade of agricultural produce; deployment of artificial intelligence, robotics and virtual facilities in teaching (such as use of drone in agricultural practical) and expanding the horizon of teachers thoughts in mitigation strategies against any unforeseen circumstance. The paper concludes that COVID-19 has opened another chapter in Nigeria’s agricultural education process and strengthening Nigeria’s agricultural education to facilitate the attainment of SDGs one and two within the shortest possible time and will guarantee employment opportunities to the teeming youth of North East Nigeria.